Governing divided societies through territorial autonomy? From (too) great expectations to a contextualist view - Kössler, Karl (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2018)
Territorial autonomy remains important for the governance of divided societies. The question is rather which understanding of it dominates the political and scholarly debate. This contribution discusses different notions of territorial autonomy that have shaped this debate. It argues that a too narrow focus on concepts of ethnic-territorial autonomy such as multinational federalism fails to recognize challenges that studies on autonomy as a prescription for governing divided societies need to face. These are the issues of secessionism, political polarization and internal minorities within the autonomous territory. The paper concludes with an assessment of the track record of autonomy and highlights the importance of taking into account for such an assessment a number of legal and non-legal context factors. Put differently, territorial autonomy itself is only one of many factors contributing to (un)successful governance of divided societies.
Keywords: etnična avtonomija; razdeljene družbe; teritorialna avtonomija; upravljanje različnosti; ustavna ureditev; večetnični federalizem